Participatory varietal selection, food security, and varietal diversity in a high-potential production system in Nepal - Joshi, Krishna D.; Witcombe, John R. (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
A survey of nearly 1500 households in the high-potential production system (HPPSs) of the Chitwan and Nawalparasi districts of Nepal showed gre.t physical and socioeconomic diversity. Varietal diversity was low in all the crops studied and varied according to location in main-season rice. Masuli was the predominant main-season rice variety, occupying over 65% of the area in Ihe surveyed villages. Seventeen modem varieties of main-season nce were introduced to farmers lo test in collaborative trials. Farmers identified 10 of the new rice varieties as having useful traits, and seven were adopted to a significant extent within three seasons. The new varieties occupied about 13% of over 800 ha of main-season rice in eight study villages and increased on-farm varietal diversity by partly replacing predominant varieties. The accepted varieties offered, on average, an 18% yield advantage without any requirement lo change agronomy or increase inputs. Other advantages of Ihe new varieties were their early maturity, drought tolerance, disease and insect tolerance, and better adaptation to different ecological niches such as areas Of shallow water. Despite the commonly assumed uniformity of high-potential production systems, the new varieties occupied specific niches in the farming system from irrigated land with varying duration of retained standing water, and from partially irrigated to rainfed lowland conditions. Farmers preferred specific varieties for different niches, which should help lo increase and maintain biodiversity on the farm. Overall production is expected to increase as each niche becomes occupied increasingly by Ihe best-adapted variety. Participatory approaches are simple, powerful method. for identifying superior varieties and deploying them in specific niches for increasing food production in high-potential production systems.